Simple House with Brick Walls and Structure System of Bamboo Reinforced Concrete, Safe and Comfortable - ., Sutarja; ., Wirawibawa; Yana, Agung (Journal of Civil Engineering, Architecture and Built Environment, 2020)
Development of appropriate housing, in the form of a simple house with concrete block walls and system of reinforced concrete structures bamboo withstand earthquakes and wind and comfortable, very necessary, because it can be built with local materials and low cost, environmentally friendly and meet the requirements are eligible to building functions, namely reliability and comfort. The construction method considers the application of six criteria for Appropriate Technology (technical, economical, ergonomic, social, cultural, energy-saving and environmentally friendly), the Systemic approach, Holistic, interdisciplinary and Participatory (SHIP), from planning to implementation to maintenance. The conclusions of this research are: 1) the material used for the structural system is concrete with a simple house f'c 20.75 MPa and a tensile strength of bamboo with a reinforcement fy amounted to 129.17 MPa, 2) application of the system of reinforced concrete structures of bamboo and walls the modest brick house technically meet the safety requirements, and 3) development simple house with concrete block walls and bamboo reinforced structural systems meet health and safety requirements that will positively affect the quality of life of its inhabitants Keywords: simple house, brick, reinforced concrete bamboo, safe, comfortable